Characterization of probiotic microorganisms in equol biotransformation - Mustafa, Salma Elghali (2012)
Metabolism of daidzin within human subject produces daidzein and equol, the metabolites which have potential health benefits against hormone-dependent diseases in humans. This study aimed to identify bacterial species for equol production from daidzin and daidzein, determine isoflavones, sugars and short chain fatty acids contents in soymilk during fermentation with selected bacteria and optimize soymilk as a medium for equol production. Seven bacteria species, namely Lactobacillus casei - 01, Lactobacillus plantarum FTCC 0350, Bifidobacterium breve ATCC 15700, Bifidobacterium longum ATCC BB536, Bifidobacterium infantis ATCC 15697, Bifidobacterium pseudocatenulatum G4 and Eggerthella lenta ATCC 43055 were screened for equol production from daidzin and daidzein. Each of the pre-cultured bacterial strains was inoculated into Brain Heart Infusion (BHI) broth containing 100 μl of daidzin and incubated anaerobically at 37° C for 48 h. In addition, B. breve ATCC 15700, B. longum ATCC BB536 and E. lenta ATCC 43055 were incubated up to 96 hours by 200 μl daidzein in similar condition. Daidzin, daidzein and equol were determined using high performance liquid chromatography. In addition, bacterial growth and formation of short chain fatty acids (lactic and acetic acid) were investigated. Daidzin was metabolized to daidzein and equol with B. breve ATCC 15700, B.longum ATCC BB536, B. infantis ATCC 15697 and L. plantarum FTCC 0350. B.pseudocatenulatum G4 and L. casei -01 were incapable to produce equol from either daidzin or daidzein, but they can metabolize daidzin to daidzein. Both of daidzein and equol were not produced when daidzin was incubated with E. lenta ATCC 43055. Since both of B. breve ATCC 15700 and B. longum BB536 ATCC provided the highest amount of equol; their daidzein metabolism was further investigated. They can produce equol within 6 hours incubation. Bacterial growth was not affected by daidzein content in the culture medium. However, incubation of the bacteria with daidzein produced more lactic and acetic acids compared to incubation without daidzein. After 96 h of incubation, the amounts of lactic and acetic acids for B. breve ATCC 15700 were at 5.53 and 8.83 mmol l-1, respectively and for B.longum BB536 were 6.86 and 7.20 mmol l-1, respectively. Subsequently, to estimate B-glucosidase enzyme activity for each of B. breve ATCC 15700, B. longum BB536, B. pseudocatenulatum G4, B. infantis ATCC 15697, L. casei -01 L. plantarum FTCC 0350 and E. lenta ATCC 43055, a single culture of the strains was inoculated in sterile soymilk for 48 h at 37º C. B. breve ATCC 15700 and B. longum BB536 offered the highest equol level and B-glucosidase activity. Therefore, fermentation of soymilk reduced its daidzin level and increased daidzein that later decreased accompanying equol production. Moreover, the heights amount of equol was obtained when soymilk was enriched with inulin and inoculated with co-culture of B. breve ATCC 15700 and B. longum BB536. Thus, fermentation of soymilk supplemented with inulin and inoculated with co-culture of B. breve ATCC 15700 and B. longum BB536 was optimized for equol production using bioreactor BIOSTAT Q-DCU3, and utilizing response surface methodology (RSM) approach. Effects of three independents variables, namely pH (4-8, X1), temperature (30-40 °C, X2) and inulin amount (0.5-1.5%, X3) on transformation of soymilk isoflavones (daidzin, Y1 and daidzein, Y2) to equol, Y3 were studied. All responses significantly (p < 0.05) fitted into quadratic models with coefficient of determination (R2) close to 1 (0.935 - 0.989). Daidzin reduction was influenced by factors in both 24 h and 48 h fermentation. Daidzein level was affected by all factors in 24 h fermentation but only by temperature in 48 h fermentation. Equol production was influenced by both pH and temperature in 24 h fermentation and by all factors in 48 h fermentation. The optimum incubation conditions for highest equol production were at pH 8, 30° C and 0.5% inulin. Model validation demonstrated there was no significant (p > 0.05) difference between the experimental and predicted values, suggested the suitability of established models in explaining the daidzin and daidzein transformation to equol as function of the pH, temperature and inulin. Besides, to study the effect of the fermentation process in soymilk oligosaccharides content, the levels of oligosaccharides in fermented soymilk were investigated. It was found that, the concentrations of oligosaccharides (stachyose and affinose) and disaccharide (sucrose) in soymilk medium decreased and followed by increment on the levels of monosaccharides (glucose, galactose and fructose) and formation of short chain fatty acids (lactic acid and acetic acid) as by-products.